Polysaccharide-Based Hydrogels for Wound Dressing: Design Considerations and Clinical Applications - Cui, Rongwei; Zhang, Luhan; Ou, Rongying; Xu, Yunsheng; Xu, Lizhou; Zhan, Xiao-Yong; Li, Danyang (Frontiers in Bioengineering and Biotechnology, 2022)
Wound management remains a worldwide challenge. It is undeniable that patients with problems such as difficulties in wound healing, metabolic disorder of the wound microenvironment and even severely infected wounds etc. always suffer great pain that affected their quality of lives. The selection of appropriate wound dressings is vital for the healing process. With the advances of technology, hydrogels dressings have been showing great potentials for the treatment of both acute wounds (e.g., burn injuries, hemorrhage, rupturing of internal organs/aorta) and chronic wounds such as diabetic foot and pressure ulcer. Particularly, in the past decade, polysaccharide-based hydrogels which are made up with abundant and reproducible natural materials that are biocompatible and biodegradable present unique features and huge flexibilities for modifications as wound dressings and are widely applicable in clinical practices. They share not only common characteristics of hydrogels such as excellent tissue adhesion, swelling, water absorption, etc., but also other properties (e.g., anti-inflammatory, bactericidal and immune regulation), to accelerate wound re-epithelialization, mimic skin structure and induce skin regeneration. Herein, in this review, we highlighted the importance of tailoring the physicochemical performance and biological functions of polysaccharide-based hydrogel wound dressings. We also summarized and discussed their clinical states of, aiming to provide valuable hints and references for the future development of more intelligent and multifunctional wound dressings of polysaccharide hydrogels.